Neighborhood racial discrimination and the development of major depression - Russell, Daniel W. (Journal of abnormal psychology, 2018)
This study examined the impact of neighborhood racial discrimination on the development of major depressive disorder (MDD) in a sample of African American women. Participants were 499 women from Georgia and Iowa with no history of MDD who were followed for 9 to 11 years. Several neighborhoodcharacteristics (community social disorder, community cohesion, and community racism) and individualcharacteristics (negative life events, financial strain, personal outlook, religious involvement, relationshipquality, negative affectivity, and individual experiences of racism) were employed as predictors of whether ornot the women met criteria for MDD during this period of time. In a multilevel logistic regression analysis,neighborhood-level discrimination as well as individual-level variables including the number of negative lifeevents, financial strain, and negative affectivity were found to be significant predictors of developing MDD. Analyses of cross-level interactions indicated that the effects of neighborhood-level discrimination were moderated by the quality of individuals’ relationships, such that better relationships with others served tolessen the effect of neighborhood discrimination on depression. Implications of these findings for understanding the negative effects of racial discrimination are discussed